Impacto pronóstico de la detección temprana de mutaciones en el dominio cinasa sobre la supervivencia de pacientes con leucemia mieloide crónica BCR-ABL positivo que reciben tratamiento con inhibidores de tirosina cinasa : revisión sistemática (2010)
ABSTRACT: Introduction The presence of BCR-ABL are important in mechanisms of resistance in CML, but the clinical benefits derived from its early detection, as a prognosis tool, have still not been demonstrated. This paper collects and systematically reviews data showing the effects of early detection of mutations on the survival of CML patients receiving treatment with tyrosine kinase inhibitors (TKI). Materials and methods We gathered randomized controlled clinical trials and corresponding data for the mutational analysis, which described the therapy phase when the analysis was done: pre-treatment, between zero and three months, or after the fourth month post-treatment with TKI. These studies provided data on the clinical phase, the overall survival, the progression-free survival and the response following for CML patients. The selected studies were published between 2001 and 2009. The search was done by two coworkers independently, using the Pubmed-Medline, Hinari and Science Direct databases. Both coworkers analyzed the information and chose trials that met the selection criteria, stored the trials using Endnote Web® software and analyzed them in a Microsoft Excel® matrix. The interesting results were described in terms of overall survival and progression-free survival index. Results Ten original articles were selected, which envolved trials including a total of 1.508 CML patients receiving first and second line TKI treatment (imatinib, dasatinib, nilotinib). The mutation type was considered a relevant factor, because the degree of resistance to treatment conferred varied among different mutation types, such as protein P-loop site and TKI binding site (T315I y F317L) mutations. We could not find any association between survival outcomes and the presence of mutations detected in the pre-treatment phase or in the first three months of therapy. We found contradictory results for the relation between the presence of late phase detected mutations and shortened survival. Additional data, such as mutation type detected, clinical phase, techniques used, patients’ classification and clonal selection, were found to have direct influence on the CML patient survival indices. Discussion and conclusions The mutations’ impact on the survival of CMS patients is multifactorial. There is, therefore, a need for studies with appropriate methodology, in order to clearly demonstrate the utility of regular monitoring of mutations emerging during the first months of therapy, to allow following and management of the CML patients, and to justify the implementation of mutation monitoring in these patients.